“Hi, Google! Tell Me A Joke”: How Google Assistant Creates Its Jokes - Atin Kurniawati; Nico Harared; Irwan Rohardiyanto (Metathesis: Journal of English Language, Literature, and Teaching, 2022)
Artificial intelligent-based application helps people in many ways, one of which telling them jokes. This study aims at (1) investigating the types of jokes on Google Assistant application, and (2) describing linguistic aspects used in the jokes. There were several steps in conducting this study. Firstly, the data of this study were the jokes taken from “tell me a joke” feature on Google Assistant. As many as 58 jokes were collected as the data. Then, the data were coded and analysed based on its linguistic aspects in terms of sounds, meanings, and word formations. After all data were analysed, conclusions were drawn. There are two forms of jokes in this application namely riddle and one liner. In riddle, the jokes are presented in question-answer form, whereas one liner joke only consists of one or two sentences. There are several linguistic aspects in creating the jokes, namely homonyms, minimal pair, substitution of sounds, onomatopoeia, phrase and words with similar pronunciation, idiomatic phrase, addition of sound and word combination. Among those aspects, homonyms are the most frequently utilized in the jokes. Jokes are beneficial for language learners to learn the real use of the language, thus further studies on jokes are suggested.